Off-Label Use of Liraglutide in the Management of a Pediatric Patient with Type 2 Diabetes Mellitus - Sara J. Micale; Michael P. Kane; Eileen Hogan (Case Reports in Pediatrics)
Liraglutide is a glucagon-like peptide 1 (GLP-1) analog indicated for the treatment of type 2 diabetes mellitus as an adjunct to diet and exercise in adults. Liraglutide lowers blood glucose levels by stimulating insulin secretion and decreasing glucagon release in glucose-dependent manners, increases satiety, and delays gastric emptying. Liraglutide, unlike metformin and insulin, is not approved for use in the pediatric population. We report the successful off-label use of liraglutide in an obese, 16 year old Caucasian female with type 2 diabetes mellitus.